İnsanın Kentinden Kentin İnsanına: Öyküde Kent, Kentleşme, Kentlileşme Görünümleri - Hergüner, Bekir (FSM Vakıf Üniversitesi, 2017)
İnsan zaman ve mekân algısıyla kuşatılmıştır. İnsan yapıp ettikleriyle mekânda kalıcı izler bırakmakta, zamanın aynasında bu izler takip edilmektedir. Mekân kurmanın ifade şekillerinden birisi olan kentleşme ve mekâna uygun davranış geliştirme anlamına gelen kentlileşme kavramları modernleşme ile birlikte dolaşıma giren kavramlardandır. Ülkemizdeki kentleşme ve kentlileşme pratiklerinden geleneğin şehirleri olumsuz bir biçimde etkilenmiştir. Öykü tür itibariyle insan gerçekliğini merkezine alır. Kentleşme ve kentlileşme de, modern insanın gerçekliğidir. Özellikle 1950’lerde başlayıp hız kesmeden devam eden kentleşme, kentlileşme hareketleri ve insanın durumu birçok öyküye konu olmuştur.

Humanity is caught up in perception of time and space and it leaves permanent traces in space through his deeds and actions. These traces can be pursued via the mirror of time. Urbanization, which is a form of expressing creation of a space, and urbanizing, which means human beings’ developing new attitudes and behaviours according to a new space, are the two terms which were introduced by modernism. The traditional cities have been adversely impacted by urbanisation practices in Turkey and also urbanizing. Characteristically, story is based on reality of humanity. Furthermore, urbanisation and urbanizing have become the realities of modern men. Starting particularly in the 1950s, urbanisation has continued to progress without a pause and has become a subject matter along with humanity and its urbanising ways.
From Human’s City to City’s Human: City, Urbanization and Views of Urbanizing
Keywords: Kent; Kentleşme; Kentlileşme; İnsan; Öykü; City; Urbanization; Urbanize; Human; Short story